Application of Behaviorism Theory in Dakwah - Qudratullah, Qudratulah (State Islamic Institute of Bone, Indonesia, 2023)
This research aims to examine the application of behaviorist theory in the practice of da'wah by exploring da'wah communication through the application of the principles of behaviorism. How the right stimulus can stimulate the desired response from the audience becomes the central question. Environmental influences, both social and cultural, are also important aspects to understand in the context of da'wah. How this environment can act as a stimulus that shapes religious behavior. This research uses qualitative research and a literature approach. Data was collected through relevant literature sources. The data has been analyzed through data reduction, data display and drawing conclusions. The results of the study show that the application of behaviorist theory in da'wah can help achieve the goals of da'wah by looking at the influence of the environment on mad’u behavior. Behaviorism emphasizes the use of da'wah methods that are more measurable, can change individual behavior significantly through stimulus and response such as the use of motivating lectures, the formation of worship habits, or the use of positive reinforcement to encourage participation in da'wah activities, by creating a relatable environment. Behaviorism theory is applied by providing reinforcement for desired or undesirable behavior in preaching. Forming habits in preaching can be done by repeating the desired behavior continuously. Classical conditioning can also be done by associating da’wah behavior with certain stimuli, such as certain environments or situations.